Pengaruh Kompetensi dan Motivasi terhadap Kinerja Karyawan pada Unit Kerja Layanan Medis Rumah Sakit Dewi Sri Karawang - Oktaviani, Anggi; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study focuses on the employees of the medical services work unit at Dewi Sri Hospital Karawang. This study aims to determine, analyze, and explain the influence of competence and motivation on employee performance in the medical services work unit of Dewi Sri Hospital Karawang. The method used in this research is quantitative with a descriptive and verificative approach. The sampling technique used is saturated sampling, with a sample of 109 people. Data collection techniques include questionnaires, observations, and literature studies. Hypothesis testing used is t-test and f-test. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of this study indicate that competence and motivation have a significant positive effect on employee performance in the medical services work unit of Dewi Sri Hospital Karawang, both partially and simultaneously.